Agrobactrium tumefaciens mediated genetic transformation in dendrobium varity sonia 17 with 1- aminocyclopropane- 1 carboxylic acid (acc) synthase antisense gene - Karthika Karunakaran (Department of Plant Biotechnology, College of Agriculture, 2006)
A study on “Agrobacterium tumefaciens mediated genetic transformation in Dendrobium sonia 17 using ACC synthase antisense gene.” was conducted at the Department of Plant Biotechnology, College of Agriculture, and Vellayani during 2004-2006.